The Role of Social Media Toward EFL Students’ Writing Skills - I Gusti Agung Vony Purnama (RETORIKA: Jurnal Ilmu Bahasa, 2024)
The landscape of higher education in Indonesia underscores the significance of English proficiency for academic advancement. Traditionally, English as a Foreign Language (EFL) instruction heavily relied on face-to-face classroom interactions guided by lecturers. However, the emergence of information technology has revolutionized learning paradigms, offering EFL students diverse opportunities beyond conventional classroom boundaries. This study investigates the pivotal role of social media platforms in enhancing the writing skills of EFL students. Utilizing a descriptive research design, data were collected from 54 participants enrolled in English III classes in 2021, focusing on English writing. Quantitative data and specific examples were gathered through questionnaires and interviews. The findings revealed a resoundingly positive response from students regarding the efficacy of social media in improving their writing skills. Furthermore, the study elucidated various benefits derived from social media use, including enhanced writing proficiency, expanded English vocabulary, and overall effectiveness as a supplementary learning tool. Thus, it is evident that social media harbors immense potential as a complementary platform for bolstering English writing skills, particularly for EFL students, offering a modern approach to language education.